2022
DOI: 10.1177/23259671221133412
|View full text |Cite
|
Sign up to set email alerts
|

Benefits of Implementing an Enhanced Recovery After Surgery Protocol in Ambulatory Surgery

Abstract: Background: Enhanced recovery after surgery (ERAS) protocols in orthopaedic surgery have garnered significant focus due to their ability to control pain adequately in the immediate postoperative window, allowing for earlier mobilization, shorter hospital stays, and fewer complications. Virginia Commonwealth University created a multimodal pain management approach in which patients receive a preoperative femoral nerve block followed by periarticular intraoperative local injection anesthesia consisting of bupiva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…7 Hailey Hampton conducted a study to analyze the application of ERAS protocols in ACL cases and concluded that after ERAS protocol application the patients were more comfortable and pain-free and could be ambulated earlier with hastened recovery. 8 R. Ramlogan et al in their study compared local anesthetic infiltration with peripheral nerve blocks and reported that the longer pain-free period and better control of the operated limb facilitated early mobilization and better patient satisfaction. 9,10 Lee etal studied a dose response curve of ropivacaine in lower limb surgeries and concluded that a comparative lower dose (ED 95 of 11.4 mg) to be effective in lower limb surgeries lasting for about 50 mins.…”
Section: Discussionmentioning
confidence: 99%
“…7 Hailey Hampton conducted a study to analyze the application of ERAS protocols in ACL cases and concluded that after ERAS protocol application the patients were more comfortable and pain-free and could be ambulated earlier with hastened recovery. 8 R. Ramlogan et al in their study compared local anesthetic infiltration with peripheral nerve blocks and reported that the longer pain-free period and better control of the operated limb facilitated early mobilization and better patient satisfaction. 9,10 Lee etal studied a dose response curve of ropivacaine in lower limb surgeries and concluded that a comparative lower dose (ED 95 of 11.4 mg) to be effective in lower limb surgeries lasting for about 50 mins.…”
Section: Discussionmentioning
confidence: 99%
“…In orthopaedic care, Hampton et al [57] explore the benefits of implementing ERAS protocols in orthopaedic surgery due to their ability to control pain adequately in the immediate postoperative window, allowing for earlier mobilisation, shorter hospital stays, and fewer complications. Virginia Commonwealth University created a multimodal pain management approach that has potential for ANPs to extend their practice.…”
Section: Theme 7: Enhanced Recovery After Surgery (Eras)mentioning
confidence: 99%